Investigating Consumers’ Attitudes on Cryptocurrency Usage as an Online Shopping Payment Method in the City of Izmir - Mesut Fenkli; Ayşe Nur Çırak; Serhat Soylu (İstanbul İktisat Dergisi)
Cryptocurrencies that are not affiliated with any certain institution or organization are currencies that cannot be physically held but can be converted into physical currency. The first cryptocurrency appeared in 2009, and since then, the intense interest in cryptocurrency around the world has led to the emergence of 10,266 different types of cryptocurrencies. Due to the intense interest in cryptocurrencies in recent years, this study, investigates consumers’ attitudes towards the use of cryptocurrencies as a payment method for online shopping based on the technology acceptance model (TAM). The study’s data were collected using the survey method applied to 212 participants in Izmir. According to the independent t-test and ANOVA applied to the obtained data, participants’ gender, educational status and occupational status were seen to not result in any were seen to not result in any significant difference regarding attitudes toward using cryptocurrencies, while their age and income status resulted in significant differences regarding their attitude. In addition, the hypotheses created for the research were tested by estimating the structural equation model (PLS-SEM), and the factors of convenience, trust, and benefit were determined to be positively related to attitude, while the factor of risk determined to be negatively related to attitude.